Dedan Cave: Extending the evidence of the Hoabinhian technocomplex in southwest China. (August 2022) - Wu, Yun; Qiu, Kaiwei; Luo, Yi; Yang, Qing; Huang, Zhijian; Wen, Jiaxin; Ji, Xueping; Li, Yinghua; Zhou, Yuduan
Highlights: A second well-dated Hoabinhian site was reported in southwest China. The first systematical typo-technological study of the Hoabinhian assemblage in China. Three major Hoabinhian reduction sequences for producing cutting tools were defined. Dedan cave provides new evidence for the "Chinese Hoabinhian Homeland" hypothesis. Abstract: The Hoabinhian technocomplex is no longer a prehistoric phenomenon limited to southeastern Asian countries since the recent report of the first Hoabinhian site in southwest China - Xiaodong rockshelter (Yunnan Province) dated as early as 43.5 ka. The site is also the earliest Hoabinhian site known in Asia so far, which makes it possible to discuss the Hoabinhian origin for the first time with reliable archaeological evidence. However, the question of whether other Hoabinhian sites could be found in southwest China to fill the tempo-spatial gap between Xiaodong rockshelter and southeastern Asian Hoabinhian sites remains to be answered. Recently, a new Hoabinhian site- Dedan cave, situated ∼ 50 km southwest of Xiaodong and dated to around 18.2–19.8 ka for the Hoabinhian levels, was discovered along the Lancang-Mekong River. The new discovery extends the evidence of the presence of the Hoabinhian technocomplex in southwest China, and its location between Xiaodong and Mainland Southeast Asia along the Lancang-Mekong River provides important new data to examine the hypothesis of North-South diffusion of the Hoabinhian along major rivers in this region of the world.